A metáfora fundamental do discurso de John Dewey - Oliveira, Daniele Cristine de; Silva, Tatiane da [UNESP]; Cunha, Marcus Vinicius da (My University, 2014)
This work aims to identify the rootmetaphor of John Dewey’s philosophical and educational discourse, by means of rhetorical analyses parameters. This methodology is founded in Aristotle and in the works of Chaïm Perelman and other contemporary authors involved in the revision of Aristotelian philosophy. The article examines the essays “The philosophical work of Herbert Spencer” and “The influence of darwinism on philosophy”, published by John Dewey respectively in 1904 e 1909. They were written in the early years of Dewey in Columbia University, which intellectual environment was not dominated by Pragmatism, and for this reason they can be considered seminal in the structuring of the author’s arguments. The analysis reveals that Dewey is favorable to Darwinian evolutionism thesis and opposite to Spencer’s one. This positioning suggests that Dewey’s discourse is bound to the metaphor “undetermined route” because it situates evolution as a process devoid of previously listed purposes at a pre-determined plan, subject only to the relations that are established, so unpredictable, between organisms and the environmental conditions that surround. Analyzing Dewey’s ideas about education, the article concludes that “undetermined route” is the rootmetaphor of Dewey’s discourse, hypothesis that can contribute to discuss Dewey in the context of contemporary philosophy.

Este trabalho visa identificar a metáfora fundamental do discurso filosófico e educacional de John Dewey, segundo os parâmetros da análise retórica. Essa abordagem metodológica é fundamentada em Aristóteles e nas obras de Chaïm Perelman e outros autores contemporâneos envolvidos na revisão da filosofia aristotélica. O artigo examina os ensaios “The philosophical work of Herbert Spencer” e “The influence of darwinism on philosophy”, publicados por John Dewey respectivamente em 1904 e 1909. Por terem sido escritos nos primeiros anos de Dewey na Universidade de Columbia, cujo ambiente intelectual não era dominado pelo Pragmatismo, esses ensaios podem ser considerados seminais no que tange estruturação dos argumentos do autor. A análise revela que Dewey é favorável às teses evolucionistas darwinistas e contrário às concepções de Spencer. Esse posicionamento sugere que o discurso de Dewey é vinculado à metá- fora “percurso indeterminado”, pois situa a evolução como processo destituído de finalidades previamente inscritas em um plano predeterminado, estando sujeito somente às relações que se estabelecem, de maneira imprevisível, entre os organismos e as condições ambientais que os circundam. Analisando as ideias de Dewey sobre a educação, o artigo conclui que “percurso indeterminado” é a metá- fora fundamental do discurso de Dewey, o que pode contribuir para discutir o autor no âmbito da filosofia contemporânea.
The rootmetaphor of John Dewey’s discourse
Keywords: Philosophy of Education; Educational Discourse; Philosophical Discourse; Rhetorical Analyses; Filosofia da Educação; Discurso Educacional; Discurso Filosófico; Análise Retórica